Criteria of validity - Adams, T (Wiley, 2024)
This article revisits the debate between inclusive and exclusive legal positivism, arguing that the question around which it is founded – about whether morality can function as a condition of legal validity – obscures a more basic and fundamental truth about the nature of law: that the norms composing a legal system's criteria of validity have a formal as opposed to substantive nature. Recognising this, I argue, helps to clarify some important aspects of the relationship between the ultimate norms of any legal system and its constitution. It also helps to explain away much of the debate between exclusive and inclusive positivism.